Brand Equity and Consumer Response in the Fast Food Industry in Port Harcourt, Rivers State, Nigeria - Hamilton- Ibama; Edith-Onajite Lolia; Horsfall, Harcourt (International Journal on Economics, Finance and Sustainable Development, 2022)
The purpose of this study is to determine the relationship between brand equity and consumer response in the fast food industry in Port Harcourt, Rivers State, Nigeria. The research adopted the descriptive survey design. The study population was 65 fast food firms registered with the Rivers State Ministry of Commerce and Industry, Port Harcourt as at May, 2021. The study accepted the entire firms as study units and employed the Taro Yamane’s formula to arrive at the sample size of 56. The simple random sampling technique was adopted to determine the respondents. A sample of 3 managers (1 marketing manager, 1 sales manager and 1supervisor) of each fast food firms weredrawn, resulting in a total of 168 respondents. One hundred and sixty-eight (168) copies of the questionnaire were administered to the respondents. However, after the error check and cleaning process, only 142 (84.5%) copies were considered as adequate and suitable for inclusion in the study. The hypotheses were tested using the Pearson’s Product Moment Correlation Coefficient and aided by the use of Statistical Package for Social Sciences (SPSS) version 25.0. The analysis revealed that there is a significant relationship between brand awareness and all the measures of consumer response. Also, the analysis revealed that there is a significant relationship between brand association and purchase intention but the relationship between brand association and brand preference is insignificant in the fast food industry in Port Harcourt, Rivers State, Nigeria. This study concludes that brand equity has significant positive effect on consumer response. The study therefore recommends that brand equity practice must be positively influenced by firms through brand strength, brand description and aimed at improving consumer response. The study also recommends that firms should realize the dimensions of brand equity that drives consumer response and emphasize on them.